Lymphoma Maxilla mimicking orbital cellulitis; case report and review of Literature - Shah, Shankar P.; Chetri, S. T.; Paudyal, Poonam; Lavaju, P.; Sah, B P; Misra, S.; Amatya, P. R. (Nepalese Journal of Ophthalmology, 2018)
Background: Sinonasal lymphomas are the commonest nonepithelial malignancies of the nasal cavity and paranasal sinuses. They may spread from their site of origin in nasal cavity and invade adjacent structures including orbits leading to varying presentation and a diagnostic dilemma. Case: A-77- year old Nepalese male presented with swelling of left eye since 1 month and pain in the same eye since 2 days. Observation: Examination revealed axial proptosis, swelling of lids, restricted extraocular movement, diffuse conjunctival and ciliary congestion with chemosis. Visual acuity was grossly decreased. The case was diagnosed as left orbital cellulitis and treated with broad spectrum intravenous antibiotics and oral steriods. There was no response despite 3 days of antibiotics and steroids therefore a computed tomography was planned which showed features of Sinonasal malignancy invading the orbit. Repeated biopsy was suggestive of malignant small round cell tumour. In the view of unclear preoperative biopsy indicating further details on the histologic type of tumor and extensive erosion of maxilla with complete loss of vision in the eye the patient was planned for Total Maxillectomy with Orbital extenteration of the left orbit. Post-operative histopathological and Immunohistochemical report were suggestive of High grade Lymphoma. The patient was advised for Adjuvant Chemotherapy and Radiotherapy, which the patient refused due to financial constraints. He is on occasional follow up since the last 6 months. Conclusions: The diagnosis of maxillary sinus lymphoma needs to be borne in mind when a clinician encounters a case of Orbital Cellulitis. It may be difficult to diagnose clinically and require radio-pathological correlation.